Discontinuous Nanoporous Membranes Reduce Non‐Specific Fouling for Immunoaffinity Cell Capture. Issue 24 (13th June 2013) - Mittal, Sukant; Wong, Ian Y.; Yanik, Ahmet Ali; Deen, William M.; Toner, Mehmet
Abstract The microfluidic isolation of target cells using adhesion‐based surface capture has been widely explored for biology and medicine. However, high‐throughput processing can be challenging due to interfacial limitations such as transport, reaction, and non‐specific fouling. Here, it is shown that antibody‐functionalized capture surfaces with discontinuous permeability enable efficient target cell capture at high flow rates by decreasing fouling. Experimental characterization and theoretical modeling reveal that "wall effects" affect cell–surface interactions and promote excess surface accumulation. These issues are partially circumvented by reducing the transport and deposition of cells near the channel walls. Optimized microfluidic devices can be operated at higher cell concentrations with significant improvements in throughput.